COMMEMORATION OF THE RUSSIAN-UKRAINIAN WAR IN VIDEO ADVERTISING - Tetiana Kovalova; Anna Oropai (Інтегровані комунікації, 2025)
The full-scale war between Russia and Ukraine has been extensively covered in the media. The representation of events influences the perception of them by current and future generations. Thus, the content related to the war, filled with meanings and narratives, constitutes a commemoration of the period of Russia's full-scale invasion of Ukraine. This influence makes advertising, as part of media discourse, responsible for shaping formats and, subsequently, consumer perceptions. The article aims to outline the specifics of transmitting narratives about the war theme in advertising that appeared in the information space during the full-scale invasion. To achieve this goal, the study employed a set of scientific methods. For formulating the theoretical foundations of the scientific article, methods of analyzing scientific sources and generalizations were used. The empirical study was conducted using content analysis and generalization of 20 video advertising examples that mention the war, Ukraine, etc., and were published from the beginning of Russia's full-scale invasion of Ukraine on February 24, 2022. Advertisers embed narratives in their information products that reinforce certain perceptions in the audience. Currently, the information and representation of events have been transferred to the Internet space, making the responsible handling of war narratives in advertising crucial. From the analysis of video ads, the most popular narratives on this topic were “Every Ukrainian can bring Ukraine's victory closer with their actions” (6 videos), “War is a threat to the present and future” (3 videos), and “Ukraine (Ukrainians) is good” (3 videos). This reflects a responsible approach to advertising and a motivational-inspirational direction in covering current circumstances.